An eye for the tropics : tourism, photography, and framing the Caribbean picturesque - Thompson, Krista A., 1972- (e-Duke books scholarly collection., 2006)
A look at the aesthetics and implications of the visual images used to sell Jamaica and the Bahamas to tourists as ""tropical paradises"" from the 1880s through the 1930s.